An Outbreak of Streptococcus pyogenes in a Mental Health Facility: Advantage of Well-Timed Whole-Genome Sequencing Over emm Typing. (9th May 2018) - Bergin, Sarah M.; Periaswamy, Balamurugan; Barkham, Timothy; Chua, Hong Choon; Mok, Yee Ming; Fung, Daniel Shuen Sheng; Su, Alex Hsin Chuan; Lee, Yen Ling; Chua, Ming Lai Ivan; Ng, Poh Yong; Soon, Wei Jia Wendy; Chu, Collins Wenhan; et al.
Abstract : OBJECTIVE: We report the utility of whole-genome sequencing (WGS) conducted in a clinically relevant time frame (ie, sufficient for guiding management decision), in managing a Streptococcus pyogenes outbreak, and present a comparison of its performance with emm typing. SETTING: A 2, 000-bed tertiary-care psychiatric hospital. METHODS: Active surveillance was conducted to identify new cases of S. pyogene s. WGS guided targeted epidemiological investigations, and infection control measures were implemented. Single-nucleotide polymorphism (SNP)–based genome phylogeny, emm typing, and multilocus sequence typing (MLST) were performed. We compared the ability of WGS and emm typing to correctly identify person-to-person transmission and to guide the management of the outbreak. RESULTS: The study included 204 patients and 152 staff. We identified 35 patients and 2 staff members with S. pyogenes. WGS revealed polyclonal S. pyogenes infections with 3 genetically distinct phylogenetic clusters (C1–C3). Cluster C1 isolates were all emm type 4, sequence type 915 and had pairwise SNP differences of 0–5, which suggested recent person-to-person transmissions. Epidemiological investigation revealed that cluster C1 was mediated by dermal colonization and transmission of S. pyogenes in a male residential ward. Clusters C2 and C3 were genomically diverse, with pairwise SNP differences of 21–45 and 26–58, and emm 11 and mostly emm 120, respectively. Clusters C2 and C3, which may have been considered person-to-person transmissions by emm typing, were shown by WGS to be unlikely by integrating pairwise SNP differences with epidemiology. CONCLUSIONS: WGS had higher resolution than emm typing in identifying clusters with recent and ongoing person-to-person transmissions, which allowed implementation of targeted intervention to control the outbreak. Infect Control Hosp Epidemiol 2018;852–860